Analisa Faktor-faktor yang mempengaruhi kecemasan pada pasien Ca Mamae dengan tindakan kemoterapi - yudono, danang tri (Viva Medika, 2019)
ABSTRACT About 39,620 women die each year from breast cancer (MOH, 2013) in Indonesia. One medical treatment in cancer patients is by chemotherapy, some side effects of chemotherapy are fission effects such as digestive disorders, hormonal disorders, and psychological effects in the form of anxiety. This study aims to determine what factors influence the level of anxiety in Ca Mamae patients with chemotherapy. This study used a descriptive correlational design with a cross sectional approach. The tool used in this study is a questionnaire adapted from the ZSAS (Zung Scale Anciety Score) instrument to measure anxiety in Ca Mamae patients with chemotherapy. The results of this study obtained factors of age, work, education, history of chemotherapy and stage of cancer is one of the causes of anxiety. From Chi Square results, age p = 0.45 (p> 0.5), education p = 95 (p> 0.05), work p = 0.85 (p> 0.05), cancer stage p = 0.000 (p <0.05), the frequency of chemotherapy p = 0.47 (p> 0.05), indicating that the most influential factor in anxiety is at the stage of cancer. Keywords: age, occupation, education, stage of cancer, frequency of chemotherapy, anxiety, chemotherapy.